A Study On Information Technology Infrastructure Library (ITIL) Implementation In Dell - Rajendran, Vinothini (2009)
This paper focuses on how the Information Technology Infrastructure Library (ITIL) standardization in Service Management can replace the traditional method, focusing on aspect such as cost and time saving. The finding of the study indicates that the ITIL framework is more cost saving than the current method.